Kinetics and mechanism of the reactions of Au(III) complexes with some biologically relevant molecules - Djeković, Ana; Petrović, Biljana; Bugarčić, Živadin D.; Puchta, Ralph; van Eldik, Rudi (Dalton Transactions, 2012)
The kinetics of the substitution reactions between the mono-functional Au(III) complexes, [Au(dien)Cl] 2+ and [Au(terpy)Cl] 2+ (dien = 3-azapentane-1,5-diamine, terpy = 2,2′;6′,2′′- terpyridine) and bi-functional Au(III) complexes, [Au(bipy)Cl 2] + and [Au(dach)Cl 2] + (bipy = 2.2′-bipyridine, dach = (1R,2R)-1,2-diaminocyclohexane) and biologically relevant ligands such as l-histidine (l-His), inosine (Ino), inosine-5′-monophosphate (5′-IMP) and guanosine-5′- monophosphate (5′-GMP), were studied in detail. All kinetic studies were performed in 25 mM Hepes buffer (pH = 7.2) in the presence of NaCl to prevent the spontaneous hydrolysis of the chloride complexes. The reactions were followed under pseudo-first order conditions as a function of ligand concentration and temperature using stopped-flow UV-vis spectrophotometry. The results showed that the mono-functional complexes react faster than the bi-functional complexes in all studied reactions. The [Au(terpy)Cl] 2+ complex is more reactive than the [Au(dien)Cl] 2+ complex, which was confirmed by quantum chemical (DFT) calculations. A more than 50% lower activation energy for the terpy than for the dien based complex was found. The bi-functional [Au(bipy)Cl 2] + complex is more reactive than the [Au(dach)Cl 2] + complex. The reactivity of the studied nucleophiles follows the same order for all studied systems, viz. l-His > 5′-GMP > 5′-IMP > Ino. According to the measured activation parameters, all studied reactions follow an associative substitution mechanism. Quantum chemical calculations (B3LYP/LANL2DZp) suggest that ligand substitution in [Au(terpy)Cl] 2+ and [Au(dien)Cl] 2+ by imidazole follows an interchange mechanism with a significant degree of associative character. The results demonstrate the strong connection between the reactivity of the complexes toward biologically relevant ligands and their structural and electronic characteristics. Therefore, the binding of gold(III) complexes to 5′-GMP, constituent of DNA, is of particular interest since this interaction is thought to be responsible for their anti-tumour activity. © The Royal Society of Chemistry 2012.
CRIS-Team Scopus Importer:2026-01-22